The critical role of ultra-low-energy vibrations in the relaxation dynamics of molecular qubits - E. Garlatti; A. Albino; S. Chicco; V. H. A. Nguyen; F. Santanni; L. Paolasini; C. Mazzoli; R. Caciuffo; F. Totti; P. Santini; R. Sessoli; A. Lunghi; et al. (Nature Communications, 2023)
Understanding phonon-induced relaxation in molecular qubits is a crucial step in realizing their application potential. Garlatti at al. use a combination of inelastic X-ray scattering and density functional theory to investigate the role of low-energy phonons on spin relaxation of a prototypical molecular qubit.